Mutations and Copy Number Abnormalities of Hippo Pathway Components in Human Cancers - He, Zhengjin; Li, Ruihan; Jiang, Hai (Frontiers in Cell and Developmental Biology, 2021)
The Hippo pathway is highly conserved from Drosophila to mammals. As a key regulator of cell proliferation, Hippo pathway controls tissue homeostasis and has a major impact on tumorigenesis. The originally defined core components of the Hippo pathway in mammals include STK3/4, LATS1/2, YAP1/TAZ, TEAD, VGLL4 and NF2. However, for most of these genes, mutations and copy number variations are relatively uncommon in human cancer. Several other recently identified upstream and downstream regulators of the Hippo signaling, including FAT1, SHANK2, Gq/11, and SWI/SNF complex, are more commonly dysregulated in human cancer at the genomic level. This review will discuss major genomic events in human cancer that enable cancer cells to escape the tumor-suppressive effects of Hippo signaling.